2005
DOI: 10.2113/gscanmin.43.6.1811
|View full text |Cite
|
Sign up to set email alerts
|

Xanes Spectroscopy of Sulfur in Earth Materials

Abstract: X-ray absorption near-edge structure (XANES) spectroscopy is the ideal non-destructive technique for characterizing and quantifying S species in compositionally complex natural materials such as silicate glasses and minerals, coals, asphalts and asphaltenes, kerogens and humic substances. Sulfur absorption edges represent the transition of S 1s and 2p core electrons to unoccupied antibonding orbitals at the bottom of the conduction band. Shifts in the position of the absorption-edge feature of S K-and L-edge X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
143
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(166 citation statements)
references
References 97 publications
22
143
1
Order By: Relevance
“…Although Li 2 S is in a more reduced state than S 8 and polysulfides, the presence of its main features in the 2473-2475.5 eV region can be explained by the ionic character of the Li 2 S bond. 49 In our qualitative analysis we will identify formation of polysulfides by the appearance of the 2470 eV feature and the formation of Li 2 S by the appearance of a convex feature at 2475.5 eV ( Figure 5). The slightly dampened shape of all the peaks indicates the presence of self-absorption, which can be explained by the use of manual grinding procedure and the resulting micrometer-sized and not the needed sub-micrometer-sized particles and/or slightly too high amount of the sulfur compound used.…”
Section: 29mentioning
confidence: 99%
“…Although Li 2 S is in a more reduced state than S 8 and polysulfides, the presence of its main features in the 2473-2475.5 eV region can be explained by the ionic character of the Li 2 S bond. 49 In our qualitative analysis we will identify formation of polysulfides by the appearance of the 2470 eV feature and the formation of Li 2 S by the appearance of a convex feature at 2475.5 eV ( Figure 5). The slightly dampened shape of all the peaks indicates the presence of self-absorption, which can be explained by the use of manual grinding procedure and the resulting micrometer-sized and not the needed sub-micrometer-sized particles and/or slightly too high amount of the sulfur compound used.…”
Section: 29mentioning
confidence: 99%
“…The XAS spectra of NiAs-structured pyrrhotite and stoichiometric troilite FeS have been measured, calculated and analyzed in a number of studies; the spectroscopic features are largely similar to those in pyrite, despite different electronic structures, and their detailed description can be found in the literature [43][44][45][46][47][48][49][50][51][52][53][54][55][56]. The main differences observed in the S K-edge XANES (Fig.…”
Section: Xanesmentioning
confidence: 99%
“…A number of XANES studies on iron sulfides have been reported previously [33,[43][44][45][46][47][48][49][50][51][52][53][54][55][56], but the difference between TEY and PFY Kedge spectra of air-oxidized and chemically etched materials has not been analyzed yet. Here, samples of each mineral (i.e., pyrite and pyrrhotite) polished in air were compared with those treated with an acidic ferric chloride solution to probe the effect of exposure to the leaching (etching) medium in hydrometallurgy and natural environments, and in materials science.…”
Section: Introductionmentioning
confidence: 99%
“…6), which arises from a 1s→ 3p transition. The location of this first transition doublet suggests that the S pπ * orbital is directly involved in the covalent Ag-S interaction [38]. This metal-sulfur bond is seen as the double feature of the first peak [39].…”
Section: Xrf and Micro-xanes Analysismentioning
confidence: 87%